Implementasi Metode EOQ dan ROP dalam Manajemen Persediaan Bahan Shoe Piston dengan Dukungan Teknologi RFID: Studi Kasus pada PT XYZ - Fitriana, Alya Rahma; Wahyudin, Wahyudin; Nugraha, Billy (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT XYZ is a manufacturing company in the automotive sector, with six production departments producing different types of spare parts. This research aims to address the stock shortages experienced by PT XYZ to prevent recurrence in the future. The methods used include linear regression for demand forecasting, EOQ and ROP methods for inventory management and determining reorder timing. The research findings indicate that linear regression is suitable for demand forecasting as it shows an increasing trend, indicating a positive relationship between time and demand. The combination of EOQ and ROP can save costs up to Rp 23,651,327,- from the initial costs as per company policy, and reduce ordering frequency to twice a year. The recommended safety stock for materials is 14 coils per month, with reorder required when stock reaches 140 coils. This research is expected to encourage the implementation of linear regression, EOQ, and ROP methods in the company, and propose the use of RFID technology for inventory monitoring in both raw material and finished goods warehouses